Blood metabolites and mineral status of sheep under silvipastoral system of grazing management - SHINDE, A K; PATNAYAK, B C; KARIM, S A; MANN, J S (The Indian Journal of Animal Sciences, 2013)
Critical physiological stages of Mutton synthetic pregnant ewes (48) were studied. They were randomised into 4 groups of 12 each, grazed 1 ha plot of 3-tier, 2-tier, single-tier silvipasture and natural rangeland. Macro (g/100 g DM) and macro (mg/kg DM) mineral conlent of herbage declined from December CCa 0.25, Cu 28.15, Mn 31.9) to March (Ca 0.21, Cu 21.02-, Mn 23.6). Serum macro(mg/100 ml) mineral level was lower during early lactation (Ca 7.21, P 3.10) compared to late gestation(ea 7.67, P 3.39), whereas micro mineral (alphag/100mI) levels were higher during early lactation (Cu 279.2, Zn 225.2, Mn 2.41) than late gestation (Cu 236.3, Zn 138.9, Mn 2.29). Blood glucose (mg%) was higher during late gestation (47.53), compared to early lactation (39.35) whereas total protein albumin and glolrulin (g%) was higher during early lactation (8.95, 4.02 and 4.56) than late gestation(6.63, 3.31 and 3.40). It is concluded that mineral contents of the pasture herbage declined with the onset of summer whereas their circulating levels remained within normal range of variation. Blood glucose level during early lactation was also low indicating additional energy supplementation during the physiological condition.